Changes in quality and bacterial profiles of Tualang and Kelulut honeys preserved by post‐harvest maturation - Yap, Shu Khang; Chin, Nyuk Ling; Niranjan, Keshavan; Shah, Nor Nadiah Abdul Karim; Than, Leslie Thian Lung (Wiley-Blackwell Publishing Ltd., 2024)
Post‐harvest maturation of two Malaysian honeys, the Tualang and Kelulut was studied by measuring changes in physicochemical and antioxidant properties, hydroxymethylfurfural (HMF) contents and bacterial profiles at room temperature of 23‐26 o C. After maturation at the recommended period of 26 weeks, water activity of both honeys increased between 0.89‐2.34% while free acidity increased between 2.05‐2.24%. Results suggested the prominence of fermentation reactions in honey during post‐harvest maturation as fructose concentration reduced by 10.6 and 1.05% for the Tualang and Kelulut honey respectively while HMF concentrations were kept at a safe limit of 48.00 and 61.23 mg/kg honey. The total phenolic content of Tualang and Kelulut honey increased significantly by 12.61 and 54.66% respectively. The highlight of this post‐harvest maturation process for Kelulut honey was the improvement found in antioxidant properties of DPPH radical scavenging activity by 10.01% to 54.74% and also the probiotic‐like potential in terms significant increase in relative abundance of the Bacillus genera to 2.6% and Lactobacillus to 6.25% at 26 weeks. The prolonged maturation process up to one year however revealed continuous accumulation of HMF to values above 80 mg/kg honey, surpassing the limits by the Codex Alimentarius Commission despite improvements of antioxidant properties and bacterial profiles.